5*-2+6-4

5*-2+6-4 is equals to -8
Solution:
Simplify the following:
6+5 (-2)-4
Multiply -2 and 5 together.
-2×5 = -10:
6+-10-4
Group the negative terms in 6-10-4 together and factor out the minus sign.
6-10-4 = 6-(10+4):
6-(10+4)
Evaluate 10+4.
10+4 = [ 14:
6-14
Factor out a negative sign in 6-14 in order to subtract.
6-14 = -(14-6):
-(14-6)
Subtract 6 from 14.
| 0 | 14
| 1 | 4
- | | 6
| 0 | 8:
Answer: |
| -8
]

Expert answered|emdjay23|Points 1525|

Question

Asked 5/28/2013 4:06:27 PM

Updated 6/27/2014 7:34:16 AM

1 Answer/Comment

Rating

3

5*-2+6-4

=(5×(0-2)+6)-4

=(5×-2+6)-4

=(-10+6)-4

=-4-4

=-8

=(5×(0-2)+6)-4

=(5×-2+6)-4

=(-10+6)-4

=-4-4

=-8

Added 6/27/2014 7:34:16 AM

This answer has been confirmed as correct and helpful.

27,687,244

questions answered

There are no comments.